Z-drug for schizophrenia: A systematic review and meta-analysis. (October 2017) - Kishi, Taro; Inada, Ken; Matsui, Yuki; Iwata, Nakao
Abstract: No systematic reviews and meta-analyses on the use of Z-drug for schizophrenia are available. Randomized, placebo-controlled, or non-pharmacological intervention-controlled trials published before 03/20/2017 were retrieved from major healthcare databases and clinical trial registries. A meta-analysis including only randomized, placebo-controlled trials was performed. Efficacy outcomes were measured as improvement in overall schizophrenia symptoms, total sleep time, and wake after sleep onset. Safety/acceptability outcomes were discontinuation rate and individual adverse events. Four trials [1 alpidem placebo-controlled study (n=66), 2 eszopiclone placebo-controlled studies (n=60), and 1 eszopiclone, shallow needling-controlled study (n=96)] were identified. The meta-analysis showed no significant differences in any outcome between pooled Z-drug and placebo treatment groups. For individual studies, alpidem was superior to placebo in improving the overall schizophrenia symptoms. One of the eszopiclone studies showed that eszopiclone was superior to placebo in improving the Insomnia Severity Index scores. Another eszopiclone study showed that eszopiclone did not differ from shallow needling therapy in improving both schizophrenia- and insomnia-related symptoms. Although this study failed to show significant benefits for the use of Z-drug in the treatment of schizophrenia, it showed that short-term use of eszopiclone is an acceptable method for treating persistent insomnia among these patients. Highlights: Systematic review and meta-analysis of Z-drug for schizophrenia were performed. Pooled Z-drug did not outperform placebo in all outcomes pertaining to efficacy and safety/acceptability. One study showed that eszopiclone was superior to placebo in improving the Insomnia Severity Index scores.